2009
DOI: 10.1002/gcc.20714
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent copy number gain of transcription factor SOX2 and corresponding high protein expression in oral squamous cell carcinoma

Abstract: Gene copy number aberrations are involved in oral squamous cell carcinoma (OSCC) development. To delineate candidate genes inside critical chromosomal regions, array-CGH was applied to 40 OSCC specimens using a microarray covering the whole human genome with an average resolution of 1 Mb. Gene copy number gains were predominantly found at 1q23 (9 cases), 3q26 (11), 5p15 (13), 7p11 (7), 8q24 (17), 11q13 (15), 14q32 (8), 19p13 (8), 19q12 (7), 19q13 (8), and 20q13 (9), whereas gene copy number losses were detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 35 publications
8
77
2
Order By: Relevance
“…Further chromosome regions of recurrent high mRNA expression detected in the present study are 14q32 and 22q13, for which DNA copy number gain has been found in previous studies in OSCC (25)(26)(27). These findings underline the assumption that high mRNA expression levels detected by CESH reflect an increase in gene transcription, which is frequently the result of distinct DNA copy number gain.…”
Section: Chromosome Bandssupporting
confidence: 87%
See 2 more Smart Citations
“…Further chromosome regions of recurrent high mRNA expression detected in the present study are 14q32 and 22q13, for which DNA copy number gain has been found in previous studies in OSCC (25)(26)(27). These findings underline the assumption that high mRNA expression levels detected by CESH reflect an increase in gene transcription, which is frequently the result of distinct DNA copy number gain.…”
Section: Chromosome Bandssupporting
confidence: 87%
“…The proto-oncogene CCNE1 is located at 19q12, it is a member of the cyclin family, which has been shown to play an important role in G1/S transition of the cell cycle. Gene copy number gain of the CCNE1 locus and high cyclin E1 protein expression was found in about 25% of OSCC cases analyzed suggesting an activation of CCNE1 by gene copy number gain (25). According to our CESH data, the most frequent high mRNA expression is found on the distal chromosome bands 19q13.1-19q13.2.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…9,15,25 Besides the lung, SOX2 has been found to be amplified and expressed in squamous cell carcinomas originating from other organ sites, predominantly derived from the embryonic foregut. 9,21,22 Recently, we found SOX2 to be amplified and expressed in squamous cell carcinomas originating from non-foregut tissues, such as the skin, the cervix, and the penis, 23 indicating that SOX2 might be a general marker for squamous cell carcinoma differentiation regardless the tissue of origin. Squamous carcinogenesis from diverse body sites may thus share similar underlying mechanisms.…”
Section: Sox2 In Squamous Cell Carcinomas From Other Organ Sitesmentioning
confidence: 96%
“…17,20 SOX2 may have similar oncogenic effects in other organs of foregut and non-foregut origin, since amplification and expression also occur in squamous cell carcinomas of the oral cavity, as well as in esophageal and gastric tumors. 9,[21][22][23] Recently, SOX2 expression has been detected in early-stage breast carcinoma. 24 These data suggest that expression of SOX2 drives oncogenesis and therefore overexpression in tumors may be associated with a more aggressive tumor phenotype and poorer clinical outcome.…”
mentioning
confidence: 99%